Comparison of the structures of the cyclotheonamide A complexes of human alpha-thrombin and bovine beta-trypsin. - Ganesh, V. (Cold Spring Harbor Laboratory Press, 1996)
Thrombin, a trypsin-like serine protease present in blood, plays a central role in the regulation of thrombosis and hemostasis. A cyclic pentapeptide, cyclotheonamide A (CtA), isolated from sponges of the genus Theonella, inhibits thrombin, trypsin, and certain other serine proteases. Enzyme inhibition data for CtA indicate that it is a moderate inhibitor of alpha-thrombin (K(i) = 1.0 nM), but substantially more potent toward trypsin (K(i) = 0.2 nM). The comparative study of the crystal structures of the CtA complexes of alpha-thrombin and beta-trypsin reported here focuses on structure-function relationships in general and the enhanced specificity of trypsin, in particular. The crystal structures of the CtA complexes of thrombin and trypsin were solved and refined at 1.7 and 2.0 A resolution, respectively. The structures show that CtA occupies the active site with the Pro-Arg motif positioned in the S2 and S1 binding sites. The alpha-keto group of CtA is involved in a tetrahedral intermediate hemiketal structure with Ser 195 OG of the catalytic triad and is positioned within bonding distance from, and orthogonal to, the re-face of the carbonyl of the arginine of CtA. As in other productive binding modes of serine proteases, the Ser 214-Gly 216 segment runs in a twisted antiparallel beta-strand manner with respect to the diaminopropionic acid (Dpr)-Arg segment of CtA. The Tyr 60A-Thr 60I insertion loop of thrombin makes a weak aromatic stacking interaction with the v-Tyr of CtA through Trp 60D. The Glu 39 Tyr and Leu 41 Phe substitutions in trypsin produce an enhanced aromatic interaction with D-Phe of CtA, which also leads to different orientations of the side chains of D-Phe and the v-Tyr. The comparison of the CtA complexes of thrombin and trypsin shows that the gross structural features of both in the active site region are the same, whereas the differences observed are mainly due to minor insertions and substitutions. In trypsin, the substitution of Ile 174-Arg 175 by Gly 174-Gln 175 makes the S3 aryl site more polar because the Arg 175 side chain is directed away from thrombin and into the solvent, whereas Gln 175 is not. Because the site is occupied by the Dpr group of CtA, the occupancy of the S3 site is better in trypsin than in thrombin. In trypsin, the D-Phe side chain of CtA fits between Tyr 39 and Phe 41 in a favorable manner, whereas in thrombin, these residues are Glu 39 and Leu 41. The higher degree of specificity for trypsin is most likely the result of these substitutions and the absence of the fairly rigid Tyr 60A-Thr 60I insertion loop of thrombin, which narrows access to the active site and forces less favorable orientations for the D-Phe and v-Tyr residues.